APPLICATION OF SIMULATION METHODS OF TEACHING INTERNAL MEDICINE TO STUDENTS OF DENTAL FACULTIES - S.Y. Kryzhanivska; V.I. Hrytsenko; T.L. Simonova (Проблеми екології та медицини)
The study of internal medicine by students of dental faculty has a number of difficulties: concentration of students’ effort and time to study core subjects, failure in (sometimes – absence of) understanding the importance of individual therapy in the practice of dentist and limited number of hours to study the subject. It has been shown that one of the variants of their solution is the use of phantoms and mannequins in training students of dental faculties